External conditions drive optimal planting configurations for salt marsh restoration. Issue 3 (3rd February 2020) - Duggan‐Edwards, Mollie F.; Pagès, Jordi F.; Jenkins, Stuart R.; Bouma, Tjeerd J.; Skov, Martin W.
Abstract: Coastal salt marshes are threatened by erosion from storminess and sea level rise, with resulting losses in flood protection, wildlife and recreational space. Although more than $1 billion has been spent to reconcile losses, restoration has had varying success because of poor survival of planted patches in challenging wave and current conditions. Marsh expansion after colonization or replanting is regulated by positive and negative feedbacks between vegetation density and sediment capture. Dense vegetation stimulates sediment capture and vertical patch growth, but negatively constrains patch expansion by concentrating hydrological energy into erosion gullies along patch edges. Conversely, low‐density vegetation may not simulate enough sediment capture, which increases plant dislodgement mortality. The strengths of positive and negative feedbacks will vary with wave exposure, but this has never been tested in natural conditions. We observed density‐dependent sediment feedbacks, survival and lateral expansion by Sporobolus anglicus patches (0.8 × 0.8 m) planted at three levels of vegetation density, at each of three levels of wave forcing (three sites). We found interactive effects of plant density and forcing on the strength of positive and negative feedbacks. Density‐dependent feedbacks only emerged in moderate and exposed conditions: classic marsh tussock patch shapes, which arise due to combined positive (vertical growth) and negative (gullies) feedbacks, were only associated with high density vegetation under exposed conditions. At high exposure, survival was enhanced by dense planting, which diverted energy away from the vegetation. In sheltered conditions, expansion was the greatest at medium density, while dense patches had high mortality and erosion. Synthesis and applications . Success of wetland restoration clearly hinges on considering interactions between environmental stress and planting density. In challenging high‐exposure settings, dense planting in large patches should maximize success, as plant facilitation boosts sediment capture and negative edge effects (gullies) will represent a diminished proportion of larger patches. Yet, benefits of dense planting will switch from positive (facilitation) to negative (competition) with reduced environmental stress, when moderate‐density planting might be optimal. Switches along stress gradients between positive and negative feedbacks are common across ecosystems. We call for wider integration of facilitation and stress–gradient principles into restoration design to safeguard restoration successes. Abstract : Success of wetland restoration clearly hinges on considering interactions between environmental stress and planting density. In challenging high‐exposure settings, dense planting in large patches should maximize success, as plant facilitation boosts sediment capture and negative edge effects (gullies) will represent a diminished proportion of larger patches. Yet, benefits of dense planting will switch from positive (facilitation) to negative (competition) with reduced environmental stress, when moderate‐density planting might be optimal. Switches along stress gradients between positive and negative feedbacks are common across ecosystems. We call for wider integration of facilitation and stress–gradient principles into restoration design to safeguard restoration successes.